DISCIPLINE DEVELOPMENT OF STUDENTS AT SCHOOL (International Conference on Elementary Education, 2018)
This literature study aims to (1) analyze the forms of disciplinary behavior by teachers and students in the teaching and learning process in schools. (2) Describe and analyze the function of each form of student discipline in school. This study is a literature study from various sources, both books and reports. This study focuses on students' discipline when the teaching and learning process takes place both in the classroom or school environment. Collecting data from various sources of books on discipline which were later cited as supporters of the preparation of the article. In his study, he did not use objects directly but rather the results of observations and the results of the experiences of the authors. This research is a research based on the results of pre-existing research related to student discipline in school. then added theoretical studies and conclusions related to Student Discipline in Schools. Here discusses the Definition of Discipline, Discipline Functions, Elements of Discipline Control, Factors that influence discipline, and Student Discipline Dimensions. It is hoped that this discussion will increase knowledge about the teaching and application of students' disciplinary attitudes at school.